An investigation of the payroll polices and its effect on the financial performance. (A case study of United Builders Merchants, Harare) - Muchingami, Tamirirashe (2017)
This research was prompted by the researcher’s observations and experience during his time at United Builders Merchants. The research was centred at investigating the payroll policies and its effects on the financial performance, a case study of UBM. The problem over emphasis on the outward looking on payroll policies and services the employees receive from the entity for the determination of their salaries and wages in relation to their production capacities. The focus was on the implementation of favourable payroll services and polices which in turn imposing positive effect to employees’ performance to increase the production capacity and therefore increasing the financial performance of the entity.The literature was reviewed referring to the research to as to achieve the objectives of the study. The field research was carried out on a selected sample size drawn from United Builders Merchants. The techniques such as questionnaires and interviews were used in the data collection process of the research. The analysed data reflected the effects of the payroll services and policies to the productivity, profitability, thus financial performance of the entity. This study recommends the company to the implementations of effective payroll services to its employees that are compatible to the situation of UBM